Locating disaster communication in changing communicative ecologies across the Pacific - Noske-Turner, Jessica; Tacchi, Jo; Horst, Heather; Papoutsaki, Evangelia (Journal of Telecommunications and the Digital Economy, 2020)
The Pacific Island region is geographically and culturally diverse, with a significant range of communication infrastructures and challenges. Access and use of mobile phones has risen exponentially over the past five years. According to ITU statistics, around 60 percent of Pacific Islanders had access to a mobile in 2012, compared to just 10 percent in 2006. In many Pacific countries mobile phones are, therefore, emerging as a key element of the local communication systems, and are being be built into disaster management and communication plans. For these plans to be effective, however, we argue that access to, and affordability of, technologies represent only one dimension of what needs to be considered in effective disaster communication plans. They also need to consider appropriate technologies, local communicative ecologies, systems for the ownership and maintenance of infrastructures, and local knowledge and belief systems. With a focus on mobile and other telecommunications technologies, this paper provides an overview of disaster communication systems and infrastructures, practices and challenges in the region.